Dificuldades enfrentadas por mulheres matemáticas: um estudo de caso realizado nas escolas do município de Capanema, estado do Pará - ALEXANDRE, Taiane da Silva (2023)
This study aims to highlight the difficulties related to the female presence in the field of mathematics. The female presence in mathematics is still quite small, both in prominent positions and in the broad spectrum of activity in the discipline. Understanding the barriers women face in this field is essential to promoting gender equality and creating a more inclusive and diverse environment. The justification for this research lies in the need to identify and understand the specific difficulties faced by female mathematicians. Gender inequality persists in many academic and professional fields, including mathematics. The lack of representativeness and the barriers faced by women can lead to female underrepresentation in leadership positions, to demotivation and early abandonment of a scientific career. Therefore, investigating these difficulties is fundamental to develop strategies and policies that promote gender equity in mathematics. To carry out this research, a mixed approach was adopted, combining quantitative and qualitative methods. Initially, statistical data were collected on the female presence in different areas of mathematics, as well as information on representativeness in academic positions and funding opportunities. In addition, interviews and questionnaires were conducted with female mathematicians in order to understand their personal experiences, identify the difficulties faced and explore possible solutions to overcome these barriers. Research carried out on the difficulties faced by female mathematicians, which revealed enriching experiences rather than significant obstacles, has great relevance for their academic training in the area of mathematics. She provides a positive perspective, offers practical knowledge, stimulates debate on gender equality and underscores the importance of diversity. These combined contributions can inspire, inform and strengthen your academic path, allowing you to develop a more comprehensive and well-grounded view of mathematics and its role in society.